Сучасна система змагань із легкої атлетики та її вплив на змагальну діяльність спортсменів високої кваліфікації - Козлова, Олена; Коzlova, Olena (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Актуальність проблеми обумовлена принципіальними змінами, що відбулися в легкій атлетиці та вплинули на систему змагань Мета роботи – підвищення результативності змагальної діяльності спортсменів високоїкваліфікації на основі систематизації знань про сучасну систему змагань із легкої атлетики. Сучасна система змагань із легкої атлетики перебуває в безперервному розвитку й характеризується розширенням спортивних календарів, появою нових форматів та категорій змагань для одержання доходів від їхнього проведення, має складну ієрархічну структуру, що поєднує змагання форматів олімпійського й професійного спорту та функціонує на міжнародному, регіональному, національному й регіональному рівнях. Отже, підвищення ефективності змагальної діяльності спортсменів високої кваліфікації припускає перехід кількісних характеристик у якісні на основі зменшення кількості змагань до 12–16 у системі річної підготовки; раціонального розподілу стартів до головних змагань (ігри Олімпіад, чемпіонати світу); підписання контрактів на участь у змаганнях у строки, які не порушують закономірностей виходу на пік готовності в головних змаганнях; оптимізації й індивідуалізації участі в зма- ганнях спортсменів високої кваліфікації; скорочення участі в серіях змагань із короткими інтервалами; припинення змагальної практики за 2–3 тижні до головних змагань чотириліття. Topicality of the work is preconditioned by the principle changes that have occurred in track and field athletics and influenced the competition system and athletes’ participation in competitions. Objective. Increase of the efficiency of competitive activity on the basis of knowledge systematizing on the modern system of track and field competitions. Results of the work. The modern system of track and field competitions is continuously developed and characterized by extension of competition calendars, appearance of new competition formats and categories for gaining profit from their conducting, has complicated hierarchical structure, unites competitions formats of Olympic and professional sport and functions on international, regional, national levels. Conclusions. Improvement of competitive activity efficiency of highly skilled athletes offers transition of quantitative characteristics into qualitative ones on the basis of: reduction of competitions to 12–16 in the system of annual preparation, rational distribution of starts before the major competitions (the Olympic Games, world championships); signing of contracts for participation in competitions in terms which do not disturb the regularities of reaching the peak performance in the major competitions; optimization and individualization of highly skilled athletes; decrease of participation in the series of competitions with short intervals; termination of competitive practice within 2–3 weeks before major competitions of four-year period.
Modern System of Competitions and its Influence on the Competitive Activity of Athletes of High Qualification
Keywords: система змагань; легка атлетика; спортсмени високої кваліфікації; system of competitions; track and field athletics; athletes of high qualification